Visions and healing in the Acts of the Apostles : how the early believers experienced God - Pilch, John J. (Collegeville, Minn. : Liturgical Press, 2004)
"This book examines religious ecstatic trance experiences and healing events reported in the Acts of the Apostles. It applies insights from the social sciences, namely: cultural anthropology, cognitive neuro-science, and medical anthropology to the interpretation of these events. It also presents Luke's continuous story-line in Acts from a literary and theological perspective. Whether or not one considers these events to be literally factual, fact-with-interpretation, or Lucan composition, the message makes plausible cultural sense to a first-century Mediterranean listener or reader."--BOOK JACKET.
Ch. 1. Acts 1-2 the journey begins : communal religious trance experiences (ASCs) -- Ch. 2. Acts 3-5 temple tours : God acts in the temple and a private home -- Ch. 3. Acts 6-12 the journey beyond Jerusalem : individuals and communal ASCs -- Ch. 4. Acts 13:1-21:36 journeys into non-Israelite territory -- Ch. 5. Acts 21:37-28:15 prisoner's progress -- Acts 28:16-31 the journey concludes -- App. 1. Outline of Acts -- App. 2. Rite and trance -- App. 3. A ceremonial rite for experiencing the realm of God in altered states of consciousness.
Includes bibliographical references (p. 160-165) and indexes.
Keywords: Bible. -- Commentaries; Visions in the Bible; Healing in the Bible